Woman to woman: an everywoman's guide to lesbian sexuality - Booth, Carol (Simon & Schuster, 2002)
Section: 288 pages : illustrations ; 22 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis